Cuticular Wax Accumulation Is Associated with Drought Tolerance in Wheat Near-Isogenic Lines - Guo, Jun; Xu, Wen; Yu, Xiaocong; Shen, Hao; Li, Haosheng; Cheng, Dungong; Liu, Aifeng; Liu, Jianjun; Liu, Cheng; Zhao, Shijie; Song, Jianmin (Frontiers in Plant Science, 2016)
Previous studies have shown that wheat grain yield is seriously affected by drought stress, and leaf cuticular wax is reportedly associated with drought tolerance. However, most studies have focused on cuticular wax biosynthesis and model species. The effects of cuticular wax on wheat drought tolerance have rarely been studied. The aims of the current study were to study the effects of leaf cuticular wax on wheat grain yield under drought stress using the above-mentioned wheat NILs and to discuss the possible physiological mechanism of cuticular wax on high grain yield under drought stress. Compared to water-irrigated (WI) conditions, the cuticular wax content (CWC) in glaucous and non-glaucous NILs under drought-stress (DS) conditions both increased; mean increase values were 151.1% and 114.4%, respectively, which was corroborated by scanning electronic microscopy images of large wax particles loaded on the surfaces of flag leaves. The average yield of glaucous NILs was higher than that of non-glaucous NILs under DS conditions in 2014 and 2015; mean values were 7368.37 kg·ha-1 and 7103.51 kg·ha-1. This suggested that glaucous NILs were more drought-tolerant than non-glaucous NILs (P = 0.05), which was supported by the findings of drought tolerance indices TOL and SSI in both years, the relatively high water potential and relative water content, and the low ELWL. Furthermore, the photosynthesis rate (Pn) of glaucous and non-glaucous wheat NILs under DS conditions decreased by 7.5% and 9.8%, respectively; however, glaucous NILs still had higher mean values of Pn than those of non-glaucous NILs, which perhaps resulted in the higher yield of glaucous NILs. This could be explained by the fact that glaucous NILs had a smaller Fv/Fm reduction, a smaller PI reduction and a greater ABS/RC increase than non-glaucous NILs under DS conditions. This is the first report to show that wheat cuticular wax accumulation is associated with drought tolerance. Moreover, the leaf CWC can be an effective selection criterion in the development of drought-tolerant wheat cultivars.